A comparative study on thermoelectric performances and energy savings of double-skin photovoltaic windows in cold regions of China. (August 2020) - Jia, Jie; Gao, Feng; Cheng, Yuanda; Wang, Peishan; EI-Ghetany, H.H.; Han, Jun
Highlights: DS-STPV windows with different ventilation modes were studied by simulations. Simulation results were experimentally validated. An optimal operational control strategy for DS-STPV windows was proposed. Benefits with the application of DS-STPV windows were demonstrated. DS-STPV window could improve the energy performance of buildings. Abstract: The use of double-skin semitransparent photovoltaic (DS-STPV) windows is well recognized as an efficient and effective approach for enhancing the building energy performance. However, despite many studies in relation to the technology have been reported so far, there are few investigations focusing on its use in cold regions. In this study, experimental measurement data for a DS-STPV window in terms of power generation and surface temperature were compared with those obtained from EnergyPlus simulations. The measured and simulated results agreed well, which confirmed the reliability of the simulation methodology adopted. On this basis, the energy performance of DS-STPV windows with non-ventilated, inner loop, and air supply ventilation modes was analyzed by simulations performed for winter conditions in cold regions. The results showed that as compared with the other two ventilation modes, the use of air supply DS-STPV windows is capable of reducing the building net electricity use by 18.5% and 20.2%, respectively. Further, an optimal control strategy for DS-STPV windows employed in cold regions was also proposed. It was found that with the use of the proposed strategy, the building net electricity use can be effectively reduced by 3.5% and 12.3%, respectively. Relevant findings of the present study provide an insight into optimal design and control of the DS-STPV windows employed in cold regions. Further, the results presented and the simulation methodology established will also be useful for further development of the technology for energy savings and emission reductions.